Pengaruh Pengetahuan, Religiusitas, dan Halal Terhadap Keputusan Memilih Melalui Attitude dan Brand Trust Pada Bakeri Modern (Studi Kasus 3 Bakeri Top Brand - Ardani Sahputra; Hanny Nurlatifah (Jurnal Al Azhar Indonesia Seri Ilmu Sosial, 2020)
Abstract : The purpose of this study was to determine the influence of knowledge, religiosity, and halal against the decision of choosing through attitude and brand trust on the 3 top brand modern bakeries. The sample used was the one who bought the product at one of the three bakeries in the last two months of 100 respondents using purposive sampling method. Data analysis method used is descriptive analysis, correspondence analysis, and path analysis. The results found that (1) knowledge, religiosity, and halal are not significantly influence the attitude of the modern bakery. (2) in the modern bakery Bakeri 1, knowledge significantly influence brand trust, while religiosity and halal are not significantly influence brand trust. In modern bakery Bakeri 2, knowledge and religiosity does not significantly affect brand trust, while halal significantly influence brand trust. In modern bakery Bakeri 3, knowledge and religiusias significantly influence brand trust, while halal not significantly influence brand trust. (3) In the modern bakery Bakeri 1, halal significantly influence the decision to choose, whereas knowledge, religiosity, attitude, and brand trust did not significantly influence the decision to choose. In modern bakery Bakeri 2, attitude, and brand trust significantly influence the decision to choose, whereas knowledge, religiosity, and halal are not significantly influence the decision to choose. In modern bakery Bakeri 3, knowledge significantly influence the decision to choose, while religiosity, halal, attitude, and brand trust did not significantly influence the decision to choose.Keywords: Knowledge, religiosity, Halal, Attitude, Brand Trust, Decision of Choosing, Brand Positioning